Pengaruh Brand Trust dan Personal Selling terhadap Keputusan Menjadi Anggota BMT Itqan - Khoerunnisa, Khoerunnisa; Komalasari, Yunika; Yuliyana, Wulan (Lembaga Yasin AlSys, 2025)
Koperasi Syariah BMT Itqan Kota Bandung is an Islamic savings and loan cooperative that provides Sharia-based financing services. However, the cooperative faces challenges in increasing its membership. This study aims to analyze the influence of brand trust and personal selling on the decision to become a member of Koperasi Syariah BMT Itqan Kota Bandung. The research employs a quantitative method with a descriptive-verificative approach. The sampling technique used is non-probability sampling with a purposive sampling approach, involving 100 active cooperative members as respondents. Data were collected using a structured questionnaire and analyzed using SPSS version 26. The results indicate that brand trust and personal selling have a positive and significant influence on the decision to become a cooperative member, both simultaneously and partially. This study provides recommendations for Koperasi Syariah BMT Itqan to enhance brand trust and the quality of personal selling interactions to attract more new members.